On one class of solutions of a countable quasilinear system of differential equations with slowly varying parameters - Shchegolev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
For a countable quasilinear differential system whose coefficients are represented as Fourier series with slowly varying coefficients and frequency, we present conditions under which solutions of this system have analogous structure.